2020
DOI: 10.1155/2020/5867627
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Glycine on the Acetic Acid-Induced Mouse Model of Colitis

Abstract: Inflammatory bowel disease, a gut disease that is prevalent worldwide, is characterized by chronic intestinal inflammation, such as colitis, and disorder of the gut microbiome. Glycine (Gly) is the simplest amino acid and functions as an anti-inflammatory immune-nutrient and intestinal microbiota regulator. This study aimed at investigating the effect of Gly on colitis induced in mice by intrarectal administration of 5% acetic acid (AA). Bodyweight and survival rates were monitored, and colonic length and weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…Consistent with previous studies, [ 30,32 ] we found that Gly administration alleviated C. rodentium ‐induced colitis. Mechanistically, this beneficial effect may be associated with the inhibition of epithelial cell apoptosis mediated by the ATF6α/CHOP signaling, inactivation of colonic inflammatory responses, and increased Lactobacillus in the colon.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with previous studies, [ 30,32 ] we found that Gly administration alleviated C. rodentium ‐induced colitis. Mechanistically, this beneficial effect may be associated with the inhibition of epithelial cell apoptosis mediated by the ATF6α/CHOP signaling, inactivation of colonic inflammatory responses, and increased Lactobacillus in the colon.…”
Section: Discussionsupporting
confidence: 93%
“…The protective effects of Gly against experimental colitis may be associated with suppressing the secretion of pro‐inflammatory cytokines. [ 30,32 ] In agreement with previous findings, the increase in pro‐inflammatory cytokines in serum was abolished by Gly. As pro‐inflammatory cytokines could facilitate inflammatory responses through the recruitment of inflammatory cells and contribute to tissue damage, the reduced infiltration of inflammatory cells was also observed in the colon tissues of mice supplemented with Gly.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…16S rDNA sequencing of cecal and colonic microbiota was used for intestinal microbiota analysis according to our previous study (Wu et al, 2020). Briefly, the DNA was extracted from cecal and colonic digesta by Qiagen QIAamp DNA Stool Mini kit (Qiagen, Hilden, Germany) according to the manufacturer's recommendation.…”
Section: S Rdna Sequencing Analysis Of Cecal and Colonic Microbiotamentioning
confidence: 99%